2017
DOI: 10.1096/fj.201700152r
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Cell‐autonomous cytotoxicity of type I interferon response via induction of endoplasmic reticulum stress

Abstract: The interaction of IFN with specific membrane receptors that transduce death-inducing signals is considered to be the principle mechanism of IFN-induced cytotoxicity. In this study, the classic non-cell-autonomous cytotoxicity of IFN was augmented by cell-autonomous mechanisms that operated independently of the interaction of IFN with its receptors. Cells primed to produce IFN by 5-azacytidine (5-aza) underwent endoplasmic reticulum (ER) stress. The chemical chaperones tauroursodeoxycholate (TUDCA) and 4-pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Specific combination strategies and their corresponding mechanisms are summarized in Table 3 [146][147][148][149][150][151][152][153][154][155]. Moreover, two-phase I clinical trials were carried out to assess the DNA methyltransferase (5-azacitidine) and HDACi (phenylbutyrate) for the treatment of hematological malignancies.…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…To date, the different mechanisms of HDACis combined with chemotherapeutic agents such as topoisomerase inhibitors, platinumbased chemotherapeutics, proteasome inhibitors, tyrosine kinase pathway inhibitors and epigenetic modifiers for advanced or drug-resistant hematological malignancies include (1) acetylating histones and inducing p21-CDK-mediated cell cycle arrest; (2) inducing apoptosis by regulating the expression of pro-and antiapoptotic genes through the intrinsic or extrinsic pathway; (3) inducing DNA damage and oxidative stress; (4) activating BTK (in CLL) or inhibiting ERK (in MM) and AKT (in CML) signaling pathways; and (5) regulating the expression of drug resistance-related molecules, such as downregulating BCR-ABL and upregulating Bim in hematological malignancies and downregulating CD44 in multiple myeloma (MM), NF-κB in ALL, γ-catenin in CML, and BRCA1, CHK1 and RAD51 in AML [126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145]. Specific combination strategies and their corresponding mechanisms are summarized in Table 3 [146][147][148][149][150][151][152][153][154][155]. Moreover, two-phase I clinical trials were carried out to assess the DNA methyltransferase (5-azacitidine) and HDACi (phenylbutyrate) for the treatment of hematological malignancies.…”
Section: The Application Of Hdacis In Malignant Hematopoiesismentioning
confidence: 99%
“…We propose that IFN-λ4 associated UPR coupled with type-III IFN signaling leads to significant ER-stress and antiproliferative effects. Some studies have shown that type-I IFNs can induce ER-stress in certain cancer cells ( 56 58 ). Although acting through different receptors, type-I and type-III IFNs induce a similar set of ISGs, supporting the idea that in the right context, type-III IFNs could induce ER-stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mRNA levels of IFN-α, IFN-β, and IFN-γ were higher in the group infected with the attenuated strain, as compared with the virulent strain, at the end of the experiment. Dysregulated type I IFN is related to inflammatory and cytotoxicity responses [68,69,70], especially IFN-β-induced liver injury via immune-mediated hepatocellular damage [71]. Therefore, further studies are required to determine whether dysregulated type I IFN plays a critical role in the pathogenicity of DHAV-3 infection.…”
Section: Discussionmentioning
confidence: 99%